Computational modelling of acetabular morphology and its implications for cup positioning - De Angelis, Sara; Henckel, Johann; Hart, Alister; Di Laura, Anna (Frontiers in Bioengineering and Biotechnology, 2025)
Achieving accurate cup positioning in total hip arthroplasty (THA) remains challenging due to the variable orientation and complex morphology of the bony acetabulum relative to the pelvis. Statistical shape modelling (SSM) has been used to describe the pelvic morphological differences that exist between sexes. However, the effect of these differences on the orientation of the cup/acetabular component in THA has not yet been investigated. The research questions this study aimed to address were i. What are the anatomical variations of the innominate bone between sexes? and ii. Do these sex-based differences have an effect on the position of the acetabular component of a hip replacement? Two sex-specific models were built on three-dimensional (3D) representations of 100 healthy bony hemipelvises (50 female and 50 male hemipelvises) which were generated from pelvic computed tomography (CT) images. Principal component analysis (PCA) was implemented to identify the main components of anatomical variation within each group, the principal components (PCs). Variability in size, shape as well as acetabular orientation of the innominate bone was found in both sex-based models. Four and five PCs accounted for 90% of the cumulative variance for the male and female models, respectively. Acetabular orientation was identified as one of the main PCs, supporting the indication that the variability commonly found in the orientation of a prosthetic acetabular component (inclination and version) is influenced by the anatomical shape of the native acetabulum. A better understanding of the relationship between innominate bone morphology and cup positioning can help plan the orientation of acetabular prosthetic components more accurately and define more personalised safe zones. Patient-specific models based on acetabular geometry can enable individualised surgical planning, potentially reducing the risk of postoperative complications such as dislocation, wear and joint instability.